Scientific Argumentation Based on the Toulmin Argumentation Pattern and Environmental Attitudes among Junior High School Students - Nur Hidayati Puspita Sari; Muhammad Syaipul Hayat; Joko Siswanto; Arifah Nur Aini; Nur Hidayati Puspita Sari; Muhammad Syaipul Hayat; Joko Siswanto; Arifah Nur Aini (Universitas Negeri Malang, 2026)
Scientific argumentation skills are an important competency in 21st century learning because they help students critically evaluate environmental issues, make evidence-based decisions, and form an attitude of caring for the environment. This study aims to analyze scientific argumentation skills, environmental concerns, and the relationship between the two in junior high school students. The research uses a quantitative approach with a correlational descriptive design. The sample consisted of 32 grade VIII students who were selected using the purposive sampling technique. Data were collected through scientific argumentation ability tests based on the Toulmin Argumentation Pattern (TAP), environmental care attitudes questionnaire based on Ugulu indicators, and observation sheets. Data analysis was carried out using descriptive statistics and Pearson correlation test. The results showed that students' scientific argumentation skills were in the low category (M = 51.74). The claim component obtained the highest scores, while warrants, backing, rebuttals, and qualifiers were still low. Environmental care is also in the less category (M = 2.20). The correlation test showed a strong and significant positive relationship between scientific argumentation ability and environmental concern (r = 0.740; p < 0.001). These findings show that improving scientific argumentation skills has the potential to support the development of environmental care attitudes. Therefore, science learning needs to integrate the Socio-Scientific Issues (SSI) and Education for Sustainable Development (ESD) approaches.